Configurações territoriais dos cursos de formação de professores de Sociologia no Brasil (1934-2017): disputas e implicações - Cristiano das Neves Bodart; Caio dos Santos Tavares (Ciências Sociais Unisinos)
This article, based on contributions from Pierre Bourdieu’s Field Theory, problematizes the spatialization of undergraduate Social Science courses and their configurations during their institutional history (1934-2017). The changes in the spatialization of the offering of these courses are highlighted and the interests at stake are shown. It is noted that the initial concentration was marked by the interests of an elite that, wishing to maintain its social distinction, sought to appropriate a (cultural) capital that could enable them to maintain their economic and political power in a modernizing society. Deconcentration, in turn, is a result of complex changes stemming from recent disputes in the political field, the rise of reformist groups, the devaluation and the increasing precariousness of the teaching career, and the expansion of the demand for Sociology teachers in all Brazilian states.